Mobilidade internacional discente: perfis e motivações do estudante estrangeiro na UFMG - Eber Feliciano de Oliveira (2018)
In the dialogue between the studies on the internationalization of higher education and the sociological approaches to international student mobility, we sought to outline the social and academic profile of foreign students enrolled at UFMG through international agreements and exchange programs at the undergraduate level in the year 2017. It was also sought to further investigate the reasons they declared for participation in international mobility programs. The research was based on secondary data obtained from the UFMG International Relations Office, as well as on primary data resulting from the application of a questionnaire (N=92) and interviews with a small group of foreign students (N=8). Regarding the profile of foreign students, there was a predominance of male students, ranging in age mainly from 21 to 24 years old, with no gainful activity, mostly from the "South" countries, with the prevalence of continents of Africa and Latin America / Caribbean. As for the areas of scientific knowledge, there was a female prevalence in Human Sciences, Languages and Arts. In terms of motivations, the results showed that students from developed countries from the "North" consider the stay abroad as an opportunity to develop dispositions of personal autonomy and discovery of other cultures, as well as a means to improve the proficiency in another language. On the other hand, students coming from less developed countries seek in the experience of international mobility, above all, an opportunity for academic qualification and expansion of their future conditions of employability. For the latter, the value and reputation of the diploma issued by the UFMG in their countries of origin were important mobilizing factors in the decision to go abroad.